PEMAHAMAN MAHASISWA PAI ANGKATAN 2018 TENTANG SUMBANG NAN DUO BALEH DAN KATO NAN AMPEK PADA PADA MATA KULIAH KEMINANGKABAUAN DI IAIN BUKITTINGGI - Varizki Syaf Putra; Iswantir M; Wedra Aprison; Arifmiboy Arifmiboy (KOLONI, 2022)
The background of this research is the strengthening of moral education or the application of character values ​​which are now very relevant to overcome the moral crisis that exists today. The moral crisis against children, youth, friends and parents, crimes against parents, behavior and ethics that are not guarded are social problems that cannot be resolved at this time. Therefore, how important is the cultivation of character in education. The approach taken in this study is a qualitative approach, because the researcher tries to describe what are the Applications of Character Education Values ​​in Minangkabauan Courses: Donations of Nan Duo Baleh and Kato Nan Ampek in Islamic Religious Education Students Class of 2018/2019 at IAIN Bukittinggi. This qualitative descriptive research is not intended to test certain hypotheses but only describes what it is about variables, symptoms or events encountered in the field. The collected data was then analyzed using qualitative analysis techniques. The results showed that the Application of Character Education Values ​​in Minangkabauan Courses: The Contribution of Nan Duo Baleh and Kato Nan Ampek to Islamic Religious Education Students Class of 2018/2019 was by using exemplary methods and habituation. So in the application of character education values ​​in the material of discordant nan duo baleh and kato nan ampek, among other things, the results of the research are: 1) students' understanding of the discordant material due to duo baleh and kato nan ampek. 2) students' interest in the discordant material by the duo baleh and kato nan ampek. 3) actualization of the values ​​of character education in the material of donating nan duo baleh and kato nan ampek 4) exemplary and habituation methods.  Keyword: Planting, character education values, donations by the duo baleh and  kato nan ampek